Empowering minds: How guided inquiry enhances scientific reasoning in students with varied self-efficacy levels - Diani, Rahma; Asyhari, Ardian; Putri, Lia Pebriana (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to determine the influence of the guided inquiry learning model on scientific reasoning abilities in students with high self-efficacy, moderate self-efficacy, and low self-efficacy categories. The method used is a quantitative approach with a quasi-experimental research type. The population was all of tenth-grade IPA (Natural Science) students. The samples taken were class XI IPA 1 and class XI IPA 2, determined with the simple random sampling technique. The research instrument consisted of description items to measure scientific reasoning ability and twenty Likert scale questionnaire items to measure student self-efficacy. The hypothesis test was conducted using the ANCOVA (Analysis of Covariance) test. Based on the hypothesis test result, the guided inquiry learning model influences students' scientific reasoning abilities with high self-efficacy, moderate self-efficacy, and low self-efficacy categories. The results of this research have several important implications for the development of educational practices, especially in science learning.